Seismic retrofitting of reinforced concrete frame-shear wall buildings using seismic isolation for resilient performance. (December 2021) - Wang, Xinyu; Xie, Linlin; Zeng, Demin; Yang, Cantian; Liu, Qianmin
Abstract: Seismic retrofitting of a reinforced concrete frame-shear wall building (RCFSWB), which is widely adopted for public buildings, is critical for the seismic risk reduction of a city. Seismic isolation is considered as an effective retrofitting method for resilient performance. The resilience-oriented retrofitting of RCFSWBs through isolation was herein investigated with emphasis on the critical design parameter, the yield ratio of the isolation system. Engineering demand parameters (EDPs) affecting resilient performance of RCFSWBs before retrofitting were identified with the consideration of different stories through two cases. The effect of the yield ratio on resilient performance after retrofitting with seismic isolation was revealed through six cases, emphasizing the control effect of critical EDPs. A yield ratio of 2% was suggested for the resilience-oriented retrofitting of RCFSWB toward the highest resilience level in the Chinese code, and was used to conduct resilience-oriented retrofitting of a nine-story RCFSWB. This research provides a valuable reference for RCFSWB retrofitting through seismic isolation.